Effect of Streblus asper Leaf Extract on Scopolamine-Induced Memory Deficits in Zebrafish: The Model of Alzheimer’s Disease - Kanathip Singsai; Natthanicha Ladpala; Natthan Dangja; Thanyaret Boonchuen; Niracha Jaikhamfu; Pirinyapat Fakthong (Advances in Pharmacological and Pharmaceutical Sciences)
Streblus asper (SA) is well known as a folk medicinal plant in Asian countries. The effect of SA extract on preventing memory impairment in zebrafish induced by scopolamine was investigated. Male zebrafish, Danio rerio, were divided into 6 groups including the control, scopolamine 200 μM (SCO), scopolamine plus rivastigmine 1.5 mg/kg (RV + SCO), and scopolamine plus SA extract at doses of 200, 400, and 800 mg/kg (SA200 + SCO, S400 + SCO, and SA800 + SCO), respectively. Spatial memory was evaluated by the colour-biased appetite conditioning T-maze test, while fear memory was measured by the inhibitory avoidance test. In the spatial memory test, results showed that the RV + SCO group had the best time spent ratio in the T-maze, followed by SA800 + SCO, SA400 + SCO, SA200 + SCO, control, and SCO group, respectively, but with no statistical significance. For the fear memory test, zebrafish that received SA at doses of 200, 400, and 800 mg/kg had significantly increased latency time as 21.75 ± 4.59, 23.75 ± 13.01, and 18.20 ± 18.84 min, respectively, when compared to the SCO group (9.80 ± 10.45 min). These results suggested that SA extract attenuated memory impairment in an inhibitory avoidance test related to fear memory. Our findings can be useful for further research to develop SA extract as a health product to ameliorate the symptoms of Alzheimer’s disease.